RESPONSE MAIZE CULTIVARS (Zea mays L) TO FOLIAR APPLICATION OF KINETIN - Nibras R. Al-Issawi; Nihad M. Abood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study aimed to investigate effect of foliar application of Kinetin on growth, yield, yield components and antioxidant affectivity of maize. A field experiment was conducted during the spring season of 2023 at the Alhamidia Research Station, College of Agriculture, University of Anbar. A randomized complete block design with split-plot arrangement with three replications was used in this study. The main plots contained the levels of kinetin (0, 25, 50, and 75 mg L-1), and the subplots contained the cultivars (Baghdad 3, Fajr 1, and Almaha). The results indicated that the maize cultivars significantly differed in most of the studied traits. The Baghdad 3 cultivar showed a significant superiority in most of the studied traits, such as leaf area (5473 cm2), highest average crop growth per unit area, and the highest grain yield (3.75 t ha-1) and biological yield. The Al-Maha cultivar showed superiority most active antioxidant enzymes, catalase and superoxide dismutase(CAT, SOD). Foliar application of kinetin improved growth traits, antioxidant enzyme activity, yield, and quality. The concentration of 75 mg L-1 recorded the best results,